Digital speckle pattern interferometry applied to a surface roughness study - Lehman, Mario (1995)
Surface roughness determination is of great interest for many applications. Several methods can be found in the literature, but most of them rely on indirect evaluation of the information, such a s photographic techniques. We propose a method to measure surface roughness that takes advantage of digital speckle pattern interferometry for obtaining the data, and of digital image processing for evaluating it. After defining the problem, a theoretical description is presented, and finally it is compared with experimental results, showing good agreement.